The role of alpha-1 and alpha-2 adrenoceptors in restraint stress-induced liver injury in mice. - Qing Zhu; Liwei Gu; Yimei Wang; Li Jia; Zengming Zhao; Shuangqing Peng; Linsheng Lei (PLoS ONE)
Acute stress affects cellular integrity in many tissues including the liver, but its underlying mechanism is still unclear. The aim of the present study was to investigate the potential involvement of catecholamines and adrenoceptors in the regulation of acute restraint stress-induced liver injury. Restraint was achieved by placing mice in restraint tubes. Mice were treated with either an α-l antagonist, prazosin, an α-2 antagonist, yohimbine, a β-l antagonist, betaxolol, a β-2 antagonist, ICI 118551, or a central and peripheral catecholamine depleting agent, reserpine, and followed by restraint stress. Assessment of liver injury (serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) , hepatic total GSH, GSSG and GSH/GSSG ratio) , histopathology and of apoptosis, by TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling) assay and western blotting, was performed. Three hours of restraint stress resulted in liver injury, as indexed by elevated serum transaminase levels, decreased hepatic total GSH levels and GSH/GSSG ratio, increased hepatic GSSG levels as well as enhanced hepatocytes apoptosis. Either reserpine or prazosin or yohimbine was found to attenuate liver injury. Furthermore, prazosin and yohimbine protected against restraint-induced hepatocytes apoptosis through attenuating the activation of caspases-9 and -3 and reducing the Bax/Bcl-2 ratio. These results suggest that α-1 and α-2 adrenoceptors mediate restraint-induced liver oxidative injury through caspase-9 and Bcl-2 family of apoptotic regulatory proteins.